Cardiometabolic diseases and active aging - polypharmacy in control - Adriana Nancy Medeiros dos Santos; Dulcineia Rebecca Cappelletti Nogueira; Beatriz Aparecida Ozello Gutierrez; Rosa Yuka Sato Chubaci; Caroline Ribeiro de Borja Oliveira
ABSTRACT Objectives: To estimate the prevalence of cardiometabolic diseases and their association with polypharmacy in elderly people at the University of the Third Age (Portuguese acronym: UnATI). Methods: A cross-sectional, descriptive, analytical study with 121 elderly patients. The prevalence ratio, Pearson's Chi-square test and Fisher's exact test were used as measures of association. Results: At the mean age of 68.3, most elderly had at least one cardiometabolic disease (82.6%), of which hypertension was the most prevalent (71.1%), and consumed prescription drugs of continuous use (92.6%). Almost half of the elderly (48.2%) used combinations of drugs, which suggests a high cardiovascular risk. Polypharmacy due to prescription was observed in almost one-third (28.6%) of the sample, associated with the use of antihypertensives (p=0.004), antidiabetics (p=0.000) or lipid-lowering agents (p<0.000). Conclusions: Clinical guidelines recommend changes in lifestyle, but increased pharmacotherapy prevails in practice, which increases the risk of adverse events, especially in old age.